2013
DOI: 10.1016/j.compstruct.2013.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Application of digital image correlation in investigating the bond between FRP and masonry

Abstract: Full characterization of the bond behavior between Fiber Reinforced Polymers (FRPs) and masonry in externally bonded reinforcement (EBR) technique is crucial at the design stage or structural performance prediction. In this regard, a full-field assessment technique seems to be valuable for an adequate characterization of the bond behavior. The digital image correlation (DIC) and feature tracking techniques have been used in this study for investigating the evolution of strains and deformation during uniaxial t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 15 publications
(31 reference statements)
1
68
0
Order By: Relevance
“…Figure 3c clearly shows the detachment of CFRP with thin layer of brick from masonry panel surface. Similar type of failure was witnesses by Bahman et al who performed single lap shear test to evaluate the deboning behavior of FRP from brick surface by using Digital Image Correlation (DIC) technique [32,33]. DIC technique is becoming popular among researchers for full-field measurement of strains and deformation by comparing the image features at different mechanical states.…”
Section: Failure Modesmentioning
confidence: 89%
“…Figure 3c clearly shows the detachment of CFRP with thin layer of brick from masonry panel surface. Similar type of failure was witnesses by Bahman et al who performed single lap shear test to evaluate the deboning behavior of FRP from brick surface by using Digital Image Correlation (DIC) technique [32,33]. DIC technique is becoming popular among researchers for full-field measurement of strains and deformation by comparing the image features at different mechanical states.…”
Section: Failure Modesmentioning
confidence: 89%
“…Damage initiation and interfacial microcracking cannot be exactly detected, while FRP debonded areas can be monitored and located during the tests from the obtained strain distribution. In SRG-strengthened specimens, the crack evolution on the mortar surface can be precisely followed during the debonding tests [15]. For on-site application, this technique could be used for short-or medium-term investigations when the FRP surface is visible and accessible and the speckle patter is protected from degradation.…”
Section: Location Of Debondingmentioning
confidence: 99%
“…DIC has been used during shear bond tests on GFRP-and SRG-strengthened bricks to obtain the evolution of strains on the FRP surface [15]. The use of active IR thermography for detection of interfacial flaws and FRP delamination induced by environmental ageing, with specimens similar to the ones used in this study, is reported in [16].…”
Section: Ndt For Debonding Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The deformation of the facet after several steps in testing is shown with respect to the reference image. Typically increasing the facet size enhances the accuracy of the measurements but will lower the spatial resolution which is defined by the facet size [38]. In this study, the specimens were prepared by applying a speckle pattern as shown in Fig.3.…”
Section: Digital Image Correlation Measurement Techniquementioning
confidence: 99%